Accessibility of Women's Empowerment in Tourism Industry from Mandalika Special Economic Zone - SYAFRUDDIN, Syafruddin; SALAHUDDIN, Muh.; NURHILALIATI, Nurhilaliati (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023, 2023)
This study aims to map the types of work, gender inequality and patterns of empowerment of female workers in the tourism service sector in the Madalika Tourism Industrial Zone, Central Lombok. Researchers used the survey method, interviews, observation, and documentation. The results of this study found that the tourism industry in the Madalika Tourism Industrial Zone has encouraged the growth of new types of jobs, business opportunities, and new entrepreneurs. South Lombok women who originally worked in the domestic sphere (unpaid work) slowly moved into the public-professional sphere. The wrong perceptions of the existence of women workers in the tourism sector have created gender inequality that is detrimental to the existence of women workers in the tourism sector. The empowerment of women's resources in the tourism sector requires a development approach based on culture and local wisdom of the community, namely strengthening the capacity of women workers, which includes strengthening individual capacity and strengthening entity (institutional) capacity. Empowerment includes building women's abilities, cultural changes and structural policies that are pro-women.